Pitfalls in clinical trials reveal need for well tolerated, more effective depigmenting agents. (3rd September 2015) - Saxena, S.; Andersen, R. M.; Maibach, H. I.
Abstract: Objective : Examine clinical trials performed for depigmenting agents in order to determine the most effective and well-tolerated depigmenting agent. Methods : We searched clinical trials, published and unpublished, performed for hydroquinone, ascorbic acid, azelaic acid, retinol and niacinamide in the period 2009 till present. Studies were examined based on participant information, design, duration, intervention, outcome measurements and statistical significance. Results : Sixty-one studies were examined, 40 published and 21 unpublished. Design, outcome measures and intervention showed sources of bias were not avoided. Only 30% of published trials were double-blind, 27% used a placebo and 80% used subjective measurements for their results. Unpublished trials follow similar outcomes, however, did not provide any significant results. Conclusion : Based on these results, we are unable to recommend a safer, more effective depigmenting agent. Lack of thorough trials limits us from accepting depigmenting agent full evaluation. To accept a depigmenting agent, its duration must test for long-term safety, clinical trial must be double-blind and comparative, use participants of the correct skin type and measure outcomes objectively. In addition, lack of results for parallel unpublished studies leaves room for discussion. Efforts toward creating more effective formulations are welcomed.